(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
The purpose of conducting this study was to prepare an oral microemulsion formulation of Rosuvastatin calcium (RC) to improve its water solubility. Oil in water microemulsion was formulated using Oleic acid, Tween 80 and Polyethylene Glycol-400(PEG-400) as oil, surfactant and co-surfactant, respectively. The ideal proportion of surfactant: co-surfactant (Smix) was chosen by constructing pseudoternary diagrams. The microemulsion formulations which proved to be stable after thermodynamic stability testing were further evaluated for physical characteristics. Selected formulations were evaluated for droplet size, zeta potential, polydispersity index, viscosity and % drug content. The results were suggestive that optimized microemulsion formulation (F2) was thermodynamically stable and clear having a droplet size of 74.29 nm and zeta potential of -18.44. In vitro dissolution study for optimized microemulsion was performed using a dialysis bag method and cumulative % drug release was determined. The result from the release study was indicative of improved solubility of Rosuvastatin calcium which may serve to boost up the oral bioavailability of drug.